Sesongvariasjon av radioaktivitet i rein. Foreløpig rapport - Eikelmann, Inger Margrethe Hætta (Rangifer, 1988)
Seasonal variation of radioactivity in Norwegian reindeer. Preliminary report. Including participants' discussion.